2017
DOI: 10.3389/fphar.2017.00090
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*57 Allele Is Associated with Concomitant Anti-tuberculosis and Antiretroviral Drugs Induced Liver Toxicity in Ethiopians

Abstract: Drug-induced liver injury (DILI) is a known adverse effect of both anti-tuberculosis (anti-TB) and antiretroviral (ARV) drugs. Recent studies highlight the implications of genetic predispositions to DILI. We performed a case-control study to identify Human Leukocyte Antigen-B (HLA-B) variant alleles associated with anti-TB and ARV co-treatment induced liver toxicity in Ethiopian TB and HIV co-infected patients. A total of 495 newly diagnosed TB and HIV co-infected patients were enrolled and received rifampicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
(64 reference statements)
0
21
1
Order By: Relevance
“…We also identified an association between CBZ‐induced SJS/TEN and HLA‐B*57:01 . This allele is a well‐known risk factor for other CD8+ T‐cell‐mediated reactions, including abacavir hypersensitivity syndrome and flucloxacillin‐induced DILI, and more recently, DILI induced by two other drug combinations, pazopanib and a combination of antituberculosis and anti‐HIV drugs . Given that the association with CBZ‐induced SJS/TEN was not genomewide significant, it needs replication in other cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also identified an association between CBZ‐induced SJS/TEN and HLA‐B*57:01 . This allele is a well‐known risk factor for other CD8+ T‐cell‐mediated reactions, including abacavir hypersensitivity syndrome and flucloxacillin‐induced DILI, and more recently, DILI induced by two other drug combinations, pazopanib and a combination of antituberculosis and anti‐HIV drugs . Given that the association with CBZ‐induced SJS/TEN was not genomewide significant, it needs replication in other cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…This allele is a well-known risk factor for other CD8+ T-cell-mediated reactions, including abacavir hypersensitivity syndrome 24,25 and flucloxacillin-induced DILI, 26 and more recently, DILI induced by two other drug combinations, pazopanib and a combination of antituberculosis and anti-HIV drugs. 27,28 Given that the association with CBZ-induced SJS/ TEN was not genomewide significant, it needs replication in other cohorts. Interestingly, our finding of the association of valine 97 with CBZ-SJS/TEN is in line with the association of valine 97 with flucloxacillin-DILI, 29 suggesting that the binding site of HLA-B*57:01 may be promiscuous for a number of drugs, which would be in keeping with the increasing number of reports of immunemediated reactions associated with this allele.…”
Section: Discussionmentioning
confidence: 99%
“…Based mainly on studies in vitro , alleles related closely to HLA‐B*57:01 , such as both HLA‐B*57:02 and HLA‐B*57:03 , are not risk factors for abacavir hypersensitivity . In view of a recent report involving an African population, which reports that HLA‐B*57:02 and HLA‐B*57:03 are risk factors for an unusual form of DILI seen when both antiretroviral and anti‐tuberculosis drugs are prescribed, as well as the strong homology in the amino acid sequence for the gene product, it is also possible that HLA‐B*57:02 and other rare B*57 alleles may be risk factors for flucloxacillin DILI. HLA‐B*57:02 , like HLA‐B*57:03 , is very rare in Northern Europeans and was not detected at all in our population but does code for V 97 in the HLA‐B gene product similar to both HLA‐B*57:01 and HLA‐B*57:03 .…”
Section: Discussionmentioning
confidence: 99%
“…PGx studies in genes coding for HLA revealed that HLA‐B*57 alleles ( B*57:03 and B*57:02 ) confer susceptibility to anti‐TB and antiretroviral drug‐induced liver toxicity . HLA‐B*57:03 is the most prevalent HLA‐B*57 subtype in black African populations, whereas HLA‐B*57:01 , which is strongly associated with abacavir‐induced hypersensitivity reaction, is absent in black Africans . HLA‐B*57:01 occurs with frequencies up to 5% in Asians and Caucasians, and prior screening for this allele is highly recommended in these populations.…”
Section: African Pharmacogenomics Research Consortium: Focus On Hiv mentioning
confidence: 99%